A proof of Hörmander's theorem for sublaplacians on Carnot groups. (October 2015) - Bramanti, Marco; Brandolini, Luca
Abstract: We give a self-contained analytical proof of Hörmander's hypoellipticity theorem in the case of left invariant sub-laplacians of Carnot groups. The proof does not rely on pseudodifferential calculus and provides intermediate regularity estimates expressed in terms of Sobolev spaces induced by right invariant vector fields.